Management of Special Non-Physical Allocation Fund in Operational Assistance for The Implementation of Equivalency Education Programme at Community Learning Center (CLC) in Semarang Regency (Educational Management, 2022)
Equivalency Education is one of the parts of non-formal education which quality has no doubt by society; it is related with the quality of the graduates, limited resources and facility, management quality of education unit, and limited fund. Since 2015, the government assistance which manifested by operational assistance fund for equivalency education has aimed to improve the education quality. But in the implementation, there was some obstacles caused by the lack of financial management quality in CLC unit and the decision factor of regional government. It is interesting to research substances related with the quality of education operational assistance fund in CLC. The aim of this study is to analyze planning process, organization, implementation, evaluation and monitoring also the impact of education operational assistance fund towards the service quality of equivalency education learning in some CLC units. This study uses descriptive qualitative approach. This study focuses on planning, organization, implementation and reporting in the management of Operational Assistance of Equivalency Education. The data collection uses the qualitative method and the data legality is done with triangulation technique through the observation, interview, documentation study, and triangulation resource. The primary data obtained from the observation to an education unit and interview with the Head of Society Education Division of Education Department, The Head of CLC units, Treasurer of CLC units, Tutor/Teacher, and also the students of equivalency program at three CLC units in Semarang Regency, they are: PKBM Mandiri, PKBM Mitra Harapan, and PKBM Kasih Ummi. The secondary data obtained from documentation study related with the management of Operational Assistance of Equivalency Education. The results showed that in the planning stage, CLCs have involved some internal and external parties to identify the learning needs in arranging school activity and fund, although some involved only selected personnel. The division of tasks and responsibilities of Operational Assistance Implementation fund has well done, but there is still a centralized management to the organizer. The usage of fund has matched with the technique guidance. The monitoring has done internally and externally by the organizer of CLC, Non-Formal Education Inspector of Regency Area Coordinator in Education Division and Education Department. The responsibility manifested as the report of the organizer to the Education Department. The impact of operational assistance implementation fund is to improve the learning service, the number of students and their motivation to study also improving the tutor performance. Based on the analyzing study results, management of operational assistance fund which consists of planning process, organizing, actuating, and monitoring in three units of CLC has well done, but there must be an improvement in organization and involvement process to a transparent implementation program and also the improvement of financial organizer in CLC unit. The impacts which emerge from operational assistance implementation fund has shown in the improvement of service quality, learning quality, the number of students and also tutor performance, but there is not an impact shown towards the quality of learning and graduates.